TRATAMENTO DE SUPERFÍCIE A BASE DE NIÓBIO PARA O ALUMÍNIO ANODIZADO COM E SEM COLORAÇÃO - Alves, Guilherme José Turcatel (2018)
Many industrial sectors need to use metallic materials with the intention of promoting the use of more efficient and sustainable equipment and structures. As application, aluminum can be used providing characteristics such as: lightness, mechanical resistance, electrical conductivity and corrosion resistance. To increase the aluminum durability, the anodizing process is the most used. Dyes are also widely used in anodized aluminum because they provide a more adherent layer, promoting greater versatility, corrosion protection and embellishment to the metallic material. In very aggressive environments, such as acidic or chloride-containing atmospheres, a more efficient protective coating is required. The ammoniacal niobium complex (NH4[NbO(C2O4)2(H2O)].nH2O) has been used as an additive in coatings to improve their resistance in these environments. This work has as main objective to develop surface treatments with ammoniacal niobium complex, for the aluminum alloy AA5052, anodized, with and without coloration. It was used the experimental design, associated with the following techniques: anodization, anodic potentiodynamic polarization, X-ray fluorescence spectroscopy, X-ray diffractometry, scanning electron microscopy, X-ray dispersive energy spectroscopy, optical microscopy, electrochemical impedance spectroscopy and Raman microscopy. The electrochemical results showed high polarization resistance (Rp) in 0.5 mol L-1 Na2SO4, pH 4, for anodized aluminum, at current density (j) in the order of 10 mA cm-2 and anodizing time (t) of 20 minutes. In the coloring process, two improved conditions were obtained: (1) t = 10 minutes and dye concentration ([C]) = 2.0 g L-1 and (2) t = 20 minutes and [C] = 1.0 g L-1. These results lead industry to economy, with reducing the use of energy or production materials. The insertion of the ammoniacal niobium complex on the anodized aluminum was applied using the sol-gel technique, followed by heat treatment of the metal surface at 350°C and 450°C without and with a heating ramp of 10°C min-1. The aluminum samples treated at 450°C allowed the tartrazine yellow dye to be inserted, thus improving corrosion protection and a metallic surface embellishment (colored). Samples treated at 350°C, without heating ramp, showed high resistance to localized corrosion (pitting) in systems containing 0.5 mol L-1 NaCl. This resistance refers to the non-existence of pitting potential throughout the electrochemical anodic section studied, when the molar ratio of NH4[NbO(C2O4)2(H2O)].nH2O of 0.15 and 0.20 was used, in relation of glycerin and citric acid, employed in the sol-gel production.